Does Profitability, Liquidity, Leverage, and Productivity Affect Sukuk Ratings? Evidence from Islamic Banks in Indonesia - Sutriawati Sutriawati; Annisa Fithria (Universitas Airlangga, 2023)
ABSTRACT This study aimed to evaluate the impact of profitability, liquidity, leverage, and productivity on Sukuk ratings within the banking sector. The study focused on Islamic Commercial Banks and Islamic Business Units in Indonesia. A purposive sampling technique was employed to select a dataset of 80 observations from Islamic Commercial Banks and Islamic Business Units rated by PT. PEFINDO between 2015 and 2019. Secondary data for the study were gathered from financial reports on the official websites of the mentioned entities and Sukuk or bond ratings issued by PT. PEFINDO, accessible through its website. The analysis utilized multiple regression analysis. The research findings indicate that profitability, liquidity, and leverage negatively impact Sukuk ratings, whereas productivity does not show a significant influence. This study contributed a distinctive approach to comprehending Sukuk ratings by thoroughly analyzing four crucial independent variables, emphasizing the Indonesian banking sector. However, the study's generalizability is limited due to its restricted timeframe and reliance on secondary data. Keywords: Profitability, Liquidity, Leverage, Productivity, Sukuk Rating ABSTRAK Penelitian ini bertujuan untuk mengevaluasi dampak profitabilitas, likuiditas, leverage, dan produktivitas terhadap peringkat Sukuk dalam sektor perbankan, khusunya pada Bank Umum Syariah dan Unit Usaha Syariah di Indonesia. Teknik purposive sampling digunakan untuk memilih kumpulan data sebanyak 80 observasi dari Bank Umum Syariah dan Unit Usaha Syariah yang dinilai oleh PT. PEFINDO antara tahun 2015 dan 2019. Data sekunder untuk penelitian ini dikumpulkan dari laporan keuangan yang tersedia di situs resmi entitas yang disebutkan dan peringkat Sukuk atau obligasi yang dikeluarkan oleh PT. PEFINDO, yang dapat diakses melalui situs webnya. Analisis menggunakan analisis regresi berganda. Temuan penelitian menunjukkan bahwa profitabilitas, likuiditas, dan leverage berdampak negatif pada peringkat Sukuk, sementara produktivitas tidak menunjukkan pengaruh yang signifikan. Penelitian ini memberikan pendekatan yang khas dalam memahami peringkat Sukuk dengan menganalisis secara menyeluruh empat variabel independen penting, dengan menekankan sektor perbankan Indonesia. Namun, generalisabilitas penelitian ini terbatas karena batasan waktu yang terbatas dan ketergantungan pada data sekunder. Kata Kunci: Profitabilitas, Likuiditas, Leverage, Produktivitas, Peringkat Sukuk